Pelatihan Bilal Tahlil dan Pendidikan Karakter pada Kader IPPNU di Desa Bekiring Ponorogo - Rahmadina Laksana Putri; Hanafi Hadi Susanto (Social Science Academic, 2023)
This study aims to determine the increase in the quality of religion and deepen the character education of IPPNU adolescents in Bekiring Village. Character education itself is a behavioral education that is formed through habitual action or habits and exemplary embodiment. To form a person with character, there must be learning or training that must be taught from an early age through dedication in the form of Bilal Tahlil training. The method used in this research is, To form a person with character, there must be learning or training that must be taught from an early age through dedication in the form of Bilal Tahlil training. The method used in this research is ABCD ( Assed community Development) in the form of providing education in the form of Bilal Tahlil training by providing guidance and assistance in learning to read Tahlil properly and correctly. The result of this training is an increase in the religious quality of IPPNU youth in Bekiring Village which can be seen by the abilities possessed by the training participants in becoming Bilal Tahlil after attending Bilal Tahlil training.